Assessing the Threat of Indonesian ISIS Returnees: An Analysis of Ideological Mindsets and Operational Capabilities - Bimantara, Angga (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
The return of Indonesian citizens formerly associated with the Islamic State of Iraq and Syria (ISIS) as Foreign Terrorist Fighters (FTF) presents a complex challenge to national security. This research analyzes the threat posed by these returnees by focusing on their ideological radicalization and operational capacity. This study utilizes a qualitative methodology, drawing data from semi-structured interviews with returnees, counter-terrorism practitioners from BNPT, Densus 88, and BIN, and academic experts. The analysis is framed by two specific theories: Randy Borum’s